PENGARUH INTELLECTUAL CAPITAL TERHADAP RETURN SAHAM DAN KINERJA KEUANGAN PADA PERUSAHAAN REAL ESTATE DAN PROPERTI YANG TERDAFTAR DI BEI TAHUN 2016-2019 - Diah Wahyuni; Anik Malikah; Afifudin Afifudin (Universitas Islam Malang, 2021)
This study was conducted to determine the effect of intellectual capital on stock returns through financial performance in real estate and property companies listed on the Indonesia Stock Exchange (IDX). This study uses a quantitative approach and uses property and real estate companies on the IDX for the 2016-2019 period as a population. The sampling method used was purposive sampling, so that there were 26 companies that met the criteria as samples. Intellectual capital variables are measured using the Value Added Intellectual Coefficient (VAICTM) method, which consists of HCE, CEE, and SCE. And investor decisions are measured by Return On Assets (ROA). While the data was processed through Microsoft Excel and SPSS 2020 software. The results of this study indicate that intellectual capital has no effect on stock returns because HCE, CEE and SCE have a sig > 0.05. Then HCE, CEE, and SCE are only one that has an influence on Return On Assets (ROA). HCE and SCE have no effect because the sig value> 0.05, while CEE has an effect with a value < 0.05. This is because the company's structural capital has not had a high contribution to the company's financial performance. The use of the company's structural capital does not affect the company's financial performance, which is proxied by Return On Assets (ROA).Keywords: intellectual capital, stock returns, Return On Assets (ROA)